Ocorrência, distribuição e reprodução de Cladocera (Crustacea: Branchiopoda) na Baía de Guanabara - RJ, Brasil - Marazzo, Andrea (1998)
The present study investigated some aspects of temporal and spatial occurrence, abundance, distributions and reproduction of marine cladocerans in Guanabara Bay (Brazil). A seasonal analysis was made on the basis of samples obtained during 1985. Three areas were distinguished within Guanabara Bay: an external area (area A), being mainly influenced by oceanic waters; an internal area (area C), being mainly influenced by fluvial waters; and a transitional area (area B) between the two. Samples were collected during horizontal surface hauls using a conical net with 200μm mesh. Two species of marine cladocerans belonging to two genera have been found to occur in study region: Penilia avirostris Dana and Evadne tergestina Claus. These species were found to be presenteei throughout the three areas investigated, but were observed to be most abundant in externai area (area A) where waters showed higher values of salinity and lower temperatures. Penilia avirostris exhtbited greater densities in summer with a peak in March, when relative greater densities of nanoplankton organisms were observed in Guanabara Bay. Evadne tergestina also showed great abundance in summer but an prominent peak density was registered in November, period of relative higher microzooplankton densities in study region. These two species exhibited a marked seasonal variation in their planktonic occurrence: Penilia avirostris disappeared of plankton from May to August, while Evadne tergestina was absent oneself in August and September. Greatest parthenogenetic brood size of Penilia avirostris was 11, while Evadne tergestina was found to carry up to 14 embryos per batch. Correlation was found between body length and brood size to Evadne tergestina, but not to Penilia avirostris. Two mouths before disappearance of cladoceran species of plankton, both Penilia avirostris and Evadne tergestina exhibited lowest mean number of parthenogenetic eggs or embryos per batch, reduction of mean body-size and sexual organisms appeared in populations. This relationship could be explained by BERG's Depression Hypothesis (1931).